Informetrics, Bradford’s Law and Citation Index - Özlem Gökkurt (Türk Kütüphaneciliği)
The author who started doing research on informetrics in 1991, aims to define Bradford's Law, which is the most intriguing of the informetric laws, in this article. The Law is described and mathematical formulations are also given. The relationship between the Law and citation indexing is explained and exemplified. The benefits of using the Law in the solution of problems concerning acquisition and circulation issues have been pointed out.